Public-private partnerships in ICT infrastructure development in South Africa - Fourie, Johannes Jacobus (My University, 2013)
ICT infrastructure is seen as one of the key drivers for economic growth. Unfortunately in South Africa many ICT infrastructure development projects fail for different reasons. Public-private partnerships (PPPs) are considered to hold much promise in theory to overcome some of the challenges ascribed to these project failures, but have proven very difficult to implement in practice. This study investigated whether the challenges of implementing ICT infrastructure development projects in South Africa can effectively be addressed by means of PPPs. In-depth, semi-structured interviews were used to obtain the views of ICT industry experts, representatives from regulatory bodies and ICT organisations, and government officials. The main findings were that PPPs could be a viable solution to overcome some of the challenges to successful implementation of ICT infrastructure projects in South Africa on condition that certain success factors that would facilitate ICT infrastructure development PPPs are present. Unfortunately some of these success factors are not currently present, therefore limiting the prospects for successful implementation of the PPP model for these projects
MBA thesis
Keywords: Public private partnerships; Information Communication and Technology